LEVEL SOCIAL SELF CONCEPT AND IMPLICATION IN GUIDANCE AND COUNSELING - Sari, Widya Kartika (Universitas Muhammadiyah Metro, 2016)
Teenager consider themselves based on the perception others and one of the element which affecting the maturation in self concept is how the assessment and social environment revenue toward it self .This study purpose to describe the self concept of teens and the implications in guidance and counseling .The research type descriptive quantitative methods. The Research was done to teenagers of simple orphanage in bengkulu with a population about 103 teenagers .The total of the research about 82 survey youth to the sample used purposive sampling techniqul instrument was used the closed of scale likert model with validity 0.873 , reliability ( 0,931 self concept ) .The findings of this research shows that: ( 1 ) self concept as of teens tend to be low category. (2) implications finding for service counseling guidance the basic of arranging the guidance counseling program service which can formed and improved the self concept of teens positively.